Índice de Apgar 0 a 3 no 1º e 5º minuto e evolução para óbito infantil: estudo populacional no Estado de São Paulo - Viau, Angela Cristina [UNIFESP] (2011)
Objective: To determine the incidence and the infant mortality in newborns with Apgar score 0-3 at both 1 and 5 minutes of life, moreover to identify demographic characteristics associated with infant death. Study Design: cohort study population in the State of Sao Paulo, Brazil collected from the database of Fundacao Seade, consisted of the Certificates of Live Births in 2006 and 2007, and the Certificates of Death from 2006 to 2008, by linking deterministic method. Included were live births without congenital malformations with Apgar score 0-3 at both 1 and 5 minutes of life, confirmed in the original Certificates of Births and/or medical records. Logistic regression was applied to determine the demographic variables present at birth associated with infant death. Results: 1,639 of 1,027,132 live births (1,6/1,000) met study criteria. The infant mortality was 70%. Of 1,075 neonatal deaths, 880 (82%) occurred within 24 hours, of which 477 in the first hour of life. The outcome to infant death was 615 (95%) of newborns with Apgar score 0 or 1 and 532 (54%) with 2 or 3 Apgar score at 5 minutes of life. Of the 25 survivors (median birth weight 3.100g) with Apgar scores of 0 at 1 and 5 minutes of life, half of them had neurological abnormalities during hospitalization. Among the 357 infants with a gestational age of 22-27 weeks and Apgar score 0 or 1 at 5 minutes, the only survivor had neurological abnormalities. In the 235 newborns with birth weight . 2500g and in the 627 premature infants with gestational ages between 22-27 weeks with Apgar score 0-3 at both 1 and 5 minutes who died, 81 (35%) in the first group and 480 (77%) in the second did not show diagnosis of intrauterine hypoxia, birth asphyxia or meconium aspiration syndrome in any line of the Certificate of Death. In the population of newborns with Apgar 0-3 at both 1 and 5 minutes, the independent variables associated with infant death were the Apgar score 0 or 1 at 5 minutes (OR 16.61; 95% CI 11.13 to 24.79), low birth weight (OR 7.52; 5.72 to 9.87), birth in outside the capital (OR 1.74; 1.30 to 2.33) in nonpublic hospital (OR 1.55; 1.18 to 2.04) and at night (OR 1.31; 1.002 to 1.71). Conclusion: This population cohort study showed high infant mortality, predominantly in the first 24 hours after delivery, associated with Apgar score 0 or 1 at 5 minutes of life and low birth weight.